2010
DOI: 10.4141/cjas09063
|View full text |Cite
|
Sign up to set email alerts
|

Effects of replacing barley grain with triticale-based dried distillers’ grains with solubles on nutrient digestibility, lamb growth performance and carcass traits

Abstract: . 2010. Effects of replacing barley grain with triticale-based dried distillers' grains with solubles on nutrient digestibility, lamb growth performance and carcass traits. Can. J. Anim. Sci. 90: 87Á98. The objective of this research was to determine the effects of increasing proportions of triticale-based dried distillers' grains with solubles (TDDGS) in the diet on nutrient digestibility, growth and carcass traits of lambs. The control diet contained 72.5% barley grain, 10.0% beet pulp, 9.0% sunflower hulls,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 42 publications
(36 reference statements)
0
15
2
Order By: Relevance
“…Less efficient gain by lambs fed WDDGS compared with those fed the control diet contrasts with previous studies in which feed efficiencies were unaffected when finishing cattle were fed up to 23% WDDGS (Beliveau and McKinnon 2008) or were improved when backgrounding steers were fed 25% WDDGS (McKinnon and Walker 2008). McKeown et al (2010) reported that feed efficiencies were not affected when lambs were fed increasing amounts of TDDGS up to 60% of diet DM.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…Less efficient gain by lambs fed WDDGS compared with those fed the control diet contrasts with previous studies in which feed efficiencies were unaffected when finishing cattle were fed up to 23% WDDGS (Beliveau and McKinnon 2008) or were improved when backgrounding steers were fed 25% WDDGS (McKinnon and Walker 2008). McKeown et al (2010) reported that feed efficiencies were not affected when lambs were fed increasing amounts of TDDGS up to 60% of diet DM.…”
Section: Discussioncontrasting
confidence: 80%
“…Similarly, McKeown et al (2010) reported that hot carcass weight and saleable meat yield were not affected by inclusion of up to 60% of TDDGS in lamb diets. Lack of differences in hot carcass weights among the diets is consistent with the lack of treatment effect on ADG.…”
Section: Carcass Traitsmentioning
confidence: 91%
“…The trend to increase proportions of vaccenic acid (VA; t11-18:1) is in agreement with a previous study reporting increases in this FA with increased concentrations of WDDGS in the diets of finishing cattle . In contrast, no variations in this FA were reported when using WDDGS (McKeown et al, 2010a) or triticale-based DDGS (McKeown et al, 2010b) in finishing lambs tail back fat. This FA is of major importance as it is the main source of rumenic acid (RA; c9, t11-18:2) via desaturation in ruminant tissues (Griinari et al, 2000) and can also undergo desaturation in humans (Scollan et al, 2006).…”
Section: Fa Profilescontrasting
confidence: 54%
“…28 The chemical analyses of the present data were in general consistent with previous studies in triticale DDGS. 2 (Tables 3 and 4). Triticale grain was lower in the rapidly degradable PA fraction (P < 0.05), the slowly degradable PB3 fraction (PB3, P < 0.01), and the unavailable PC fraction (P < 0.01) and higher in the rapidly degradable PB1 fraction (P < 0.01) and the intermediately degradable PB2 fraction (P < 0.05) than triticale DDGS.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…The nylon bags were placed into a polyester mesh bag (45 cm × 45 cm attached to a 90 cm length of rope) and suspended in the rumen. Bags were added into the rumen according to a "gradual addition/all out" schedule and were incubated for 48, 24,12,8,4,2, and 0 h. 10 The number of bags increased with the length of incubation to ensure that sufficient residue was available for analysis. After incubation, the bags were collected from the rumen and washed under a cold water stream without detergent to remove rumen fluid.…”
Section: ■ Introductionmentioning
confidence: 99%